Consumption-Savings Pattern of Low Income Households towards a Sustainable Livelihood – A Gender Perspective - Mohd, Saidatulakmal; Shakil, Nurul Syifaa Mohd; Azhar, Nur Azirah Zahida Mohamad (Universiti Sains Malaysia, 2016)
A report by Khazanah Research Institute on the State of Households in 2015 revealed that majority of Malaysian households owned items such as cars, motorcycles, refrigerators, televisions, mobile phones, satellite TVs and internet subscriptions and that most low-income households acquired these items and services on credit. The report further concluded that this trend was also accompanied by low personal savings. While strong income growth has in turn, helped alleviate poverty and added to the legions of the middle-income, incidentally, this has fuelled consumption; with households increasingly use debt for spending. Interestingly, low-income households do not only have low personal savings due to high consumption, but low personal savings due to high consumption of assets (productive and non productive) that act as buffers against any unanticipated events such as loss of job or income. By using a structured questionnaire on 300 low-income households, the objectives of the study are (i) to examine the consumption-savings pattern of low-income households and (ii) to assess the consumption-savings pattern between genders. Low-income households are identified as households earning MYR 3,600 per month. Data gathered on personal savings include cash savings, savings for pilgrimage, gold, kut (rotational savings scheme), community death benefits, land and property